PENGARUH PEMBERIAN Plant Growth Promoting Rhizobacteria (PGPR) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KAILAN (Brassica oleraceae var. Acephala) SISTEM VERTIKULTUR - Oktaviani, Evi; Sholihah, Siti M (Aksara Public, 2018)
Abstract Kailan (Brassica oleraceae var Acephala) is one of vegetable commodity which is quite popular and sought after by Indonesian society because it has high enough nutrient content. One important factor that can affect the growth and yield of a plant is the availability of nutrients. Nutrient nutrients can be increased in soil availability with growth-promoting bacteria and plant health. Therefore, Plant Growth Promoting Rhizobacteria (PGPR) is given to the soil to increase the availability of nutrients. There has been no recommendation regarding the right dosage of PGPR for Kailan plants. This research aims to determine the effect of PGPR on growth and yield of Kailan plants and to know the exact dosage of PGPR. The design was Randomized Block Design (RAK), consisting of 4 treatments and 6 replications, namely: P0 (without PGPR), P1 (100 ml PGPR / plant), P2 (150 ml PGPR / plant), P3 (200 ml PGPR /plant). The variables observed were plant height, number of leaves, fresh weight, and root length of the plant. The results showed that PGPR had a very significant effect on the growth and yield of kailan plants, where 200 ml of PGPR treatment gave growth and yield of the highest kailan plants and without PGPR gave the lowest yield.